Genetic Method for Labeling Electrically Coupled Cells: Application to Retina - Qiao, Mu; Sanes, Joshua R. (Frontiers in Molecular Neuroscience, 2016)
Understanding how the nervous system functions requires mapping synaptic connections between neurons. Several methods are available for imaging neurons connected by chemical synapses, but few enable marking neurons connected by electrical synapses. Here, we demonstrate that a peptide transporter, Pept2, can be used for this purpose. Pept2 transports a gap junction-permeable fluorophore-coupled dipeptide, beta-alanine-lysine-N-7-amino-4-methyl coumarin-3-acid (βALA). Cre-dependent expression of pept2 in specific neurons followed by incubation in βALA labeled electrically-coupled synaptic partners. Using this method, we analyze light-dependent modulation of electrical connectivity among retinal horizontal cells.